2007
DOI: 10.1364/oe.15.004452
|View full text |Cite
|
Sign up to set email alerts
|

Generalized formulation for performance degradations due to bending and edge scattering loss in microdisk resonators

Abstract: We present a generalized formulation for the treatment of both bending (whispering gallery) loss and scattering loss due to edge roughness in microdisk resonators. The results are applicable to microrings and related geometries. For thin disks with radii greater than the bend-loss limit, we find that the finesse limited by the scattering losses induced by edge roughness is independent of radii. While a strong lateral refractive index contrast is necessary to prevent bending losses, unless the radii are of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…The effective refractive index (n eff ) of the lowest order waveguide mode is usually more than 1.5 times smaller than n s . The reduction in n eff introduces large radiation loss in WGM and cavity Q is reduced drastically especially for sub-wavelength diameter, D [10]. The metal-capped microdisk structure has been proposed to increase n eff and therefore Q [11].…”
Section: Introductionmentioning
confidence: 99%
“…The effective refractive index (n eff ) of the lowest order waveguide mode is usually more than 1.5 times smaller than n s . The reduction in n eff introduces large radiation loss in WGM and cavity Q is reduced drastically especially for sub-wavelength diameter, D [10]. The metal-capped microdisk structure has been proposed to increase n eff and therefore Q [11].…”
Section: Introductionmentioning
confidence: 99%
“…In order to realize high-Q ring resonators, the bend radii of the ring resonators have to be large enough to avoid the dominant bending loss. The model shows that the optical mode is better confined at shorter wavelengths and thus allows smaller bend radius without bending loss; however, the scattering loss at shorter wavelengths is higher [19]. For 5.3-μm-wide and 50-nm-thick Si 3 N 4 waveguides, the radii have to be larger than 7 mm, 3 mm, and 2 mm in 1550nm, 1310nm, and 1060nm wavelength regimes to have negligible bending loss, and their corresponding scattering-limited losses are 0.4 dB/m, 0.8 dB/m, and 2.1 dB/m.…”
Section: Design Of High-q Ring Resonatorsmentioning
confidence: 98%
“…This has a positive effect on the scattering loss and the coupling efficiency. It can be shown that taking into account the large vertical confinement, the scattering loss, which is caused by the sidewall roughness of the microdisk, scales roughly linearly with the thickness of the device [32]. The coupling efficiency to the underlying waveguide also increases for a thinner structure, because there exists a larger exponential tail in the cladding, and thus, also a larger overlap with the silicon waveguide.…”
Section: B Improved MDL Design and Operationmentioning
confidence: 99%